Data from: Photosynthetic and phenological responses of dwarf shrubs to the depth and properties of snow - Saarinen, Timo; Rasmus, Sirpa; Lundell, Robin; Kauppinen, Olli-Kalle; Hänninen, Heikki (Zenodo, 2015)
Snow is known to have a major impact on vegetation in arctic ecosystems, but little is known about how snow affects plants in boreal forests, where the snowpack is uneven due to canopy impact. The responses of two dwarf shrubs, the evergreen Vaccinium vitis-idaea and the deciduous V. myrtillus, to snow conditions were studied in a snow manipulation experiment in southern Finland. The thermal insulation of the snowpack was expected to decrease with partial removal or compression of the snow, while addition of snow was expected to have the opposite effect. The penetration of light was manipulated by partial removal of snow or by formation of an artificial ice layer in the snowpack. CO2 exchange measurements that were carried out at the time of maximum snow depth in late March indicated significant photosynthetic activity in the leaves of V. vitis-idaea under snow. Net gain of CO2 was observed in the daytime on all the manipulation plots, excluding the snow addition plots, where light intensity was very low. The subnivean photosynthesis compensated for a substantial proportion (up to 80%) of the respiratory CO2 losses. Chlorophyll fluorescence measurements indicated reduced potential capacity of photosystem II in the leaves of V. vitis-idaea on those plots where snow cover was thin. Neither V. vitis-idaea nor V. myrtillus suffered from frost damage (assessed as electrolyte leakage) when thermal insulation was reduced by means of snow manipulations. No phenological responses were observed in V. vitis-idaea, but in V. myrtillus bud burst, leaf unfolding and flowering were advanced by 1–3 days on the addition plots. The results of the present study show that dwarf shrubs respond to not only the thickness of snow but also the physical properties of snow, both of which are expected to change due to climatic warming. Saarinen et al_oikos Field data collected for the paper 10.1111/oik.02233. For details, see ReadMe.txt.